Trans-Boundary Water Sharing Issues: A Case of South Asia - Iram Khalid (Journal of Political Studies, 2010)
The water issue is gradually becoming the prime focus between the interstate relations. Increasing water shortage has made South Asia a water-stressed region. South Asia has four major rivers basins. They originate from Himalayas and irrigation of vast area of this region; thereby provide edibles and livelihood to the huge population. The four main co-riparian states of the region are India-Pakistan and India– Bangladesh-Nepal are lying in west and east respectively. Water shortage is becoming the bone of contention in this region. With the growing population, industrial, agricultural and domestic uses, glaciers are melting and causing environmental degradation. Conflicts over water issue are growing among the countries and the people of this area. The question of hydropower generation and commercial irrigation is issue of great concern and a source of controversy. The present paper is an attempt to analyze this issue. The outcome of this research reflects that no single policy option will eradicate the conflicts on water shortage; rather a multidimensional and coordinated strategy is required to address the emerging challenges.